Transkulturasi Social Capital Pesantren - Ahmad Fauzi (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
The presence of pesantren, since several centuries ago has significantly contributed to the middle of social life, this view can not be separated from the role of pesantren as the last moral bastion, as well as the oldest educational system in Indonesia. Sociologically, the role of pesantren gives birth to a value system in the form of local wisdom values, and as a belief and core values subculture in building a moderate Islamic education paradigm. Such social value system is the construction of individual social thought and action based on al-Qur'an and al-Hadith and socio-cultural society. Therefore, the pesantren value system becomes the root of social culture and has transculturated to become (social capital) in giving birth to the moderate Islamic education paradigm. Thus to provide a holistic understanding of this study, the author uses the theory (social construction) between the dialectic of externalization, objectivation and internalization. In that theory, habitualization of the above values is part of the externalization process which is believed to be the objectivation in the social reality of society as the value system (internalization) of pesantren. Thus, the internalization of the aforementioned values becomes social capital for pesantren to build moderate Islamic education. Because essentially, the portrait of Islamic education is always in contact with the social reality surrounding it (historical determinism and practical realism), this view can give birth to a moderate Islamic education paradigm that is believed to be cultural enlightenment by promoting the principle of togetherness (ijtima'iyyah) justice (is), tolerance (tasamuh) consent (shura) to social liberation (taharrur)